Thermal and spectroscopic properties of Er3+: Lu2SiO5 and characteristics of its in-band pumped laser. (5th November 2015) - Ding, Y C; Di, J Q; Bai, Y J; Nakai, Y; Tsuboi, T
Abstract: We investigated the thermal properties and Stark-level energies of Er 3+ :Lu2 SiO5 crystal and its in-band laser-pumped CW laser. The thermal conductivity, which was calculated by the thermal diffusion coefficient and the specific heat, decreased from 5.3 to 3.2 Wm −1 k −1 with the temperature increasing from 298.15 to 573.15 K. From the low temperature absorption spectra at 10 K and photoluminescence spectrum at 12 K, the Stark level energies of Er 3+ were obtained for the ground state and many excited states. Under pumping by a 1536 nm laser with 4.4 W power, a 1596 nm CW laser with maximum output power of 610 mW was obtained, corresponding to a slope efficiency and optical efficiency of 16.3 % and 13.9 %, respectively.